2001
DOI: 10.1086/319356
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of an Infant with Chromobacterium violaceum Sepsis

Abstract: Chromobacterium violaceum sepsis, a rarely reported phenomenon, has a high mortality rate. We report a unique case of C. violaceum sepsis in an infant. A 4-month-old girl presented to our institution with fever, pustular skin lesions, and distended abdomen, as well as diminished activity and mental status. Radiological investigation revealed brain, lung, and hepatic abscesses. The infant was successfully treated with trimethoprim-sulfamethoxazole and ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 18 publications
(21 reference statements)
0
40
0
5
Order By: Relevance
“…O quadro clínico apresentado assim como os exames hematológicos, ultrasonografia, tomografia computadorizada de abdômen e radiografia de tórax e o laudo do exame cadavérico realizado no segundo óbito apresentaram achados também encontrados por Midani 12 e Chen 2 Os cortes histológicos com presença de múltiplas coleções de piócitos e grumos bacterianos em área necrosada demonstram a agressividade e virulência da bactéria em provocar quadros graves. Esta doença, quando precocemente identificado e conveniente e oportunamente tratados aumentam em sobremaneira a sobrevida do paciente 13 Para que isso ocorra é de fundamental importância que a investigação epidemiológica seja conduzida de forma rápida, integrada para que possa dar respostas imediatas que controlem o evento e evite o surgimento de novos casos. Acredita-se que a sobrevivência desse último paciente deve-se em muito as conclusões advindas da investigação epidemiológica e laboratorial que nortearam o sucesso das condutas terapêuticas instituídas pela equipe médica.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O quadro clínico apresentado assim como os exames hematológicos, ultrasonografia, tomografia computadorizada de abdômen e radiografia de tórax e o laudo do exame cadavérico realizado no segundo óbito apresentaram achados também encontrados por Midani 12 e Chen 2 Os cortes histológicos com presença de múltiplas coleções de piócitos e grumos bacterianos em área necrosada demonstram a agressividade e virulência da bactéria em provocar quadros graves. Esta doença, quando precocemente identificado e conveniente e oportunamente tratados aumentam em sobremaneira a sobrevida do paciente 13 Para que isso ocorra é de fundamental importância que a investigação epidemiológica seja conduzida de forma rápida, integrada para que possa dar respostas imediatas que controlem o evento e evite o surgimento de novos casos. Acredita-se que a sobrevivência desse último paciente deve-se em muito as conclusões advindas da investigação epidemiológica e laboratorial que nortearam o sucesso das condutas terapêuticas instituídas pela equipe médica.…”
Section: Discussionunclassified
“…A taxa de letalidade é bastante elevada, sendo em torno de 41%, no período de 1980 a 1994, nos Estados Unidos 12 . Esta gravidade da doença deve-se a uma endotoxina produzida pela bactéria 13 , condicionada por uma deficiência imunológica do paciente principalmente a doença crônica granulomatosa 1 .…”
unclassified
See 1 more Smart Citation
“…C. violaceum, a Gram-negative motile saprophytic bacterium, has been mainly isolated from soil and water in tropical and subtropical regions (Koburger & May 1982;Richard 1993). Some researchers have reported that C. violaceum is found between latitudes 358N and 358S (Macher et al 1982;Moore et al 2001;Dromigny et al 2002). In these regions, it is thought to be a member of the natural flora in waters and soils.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note that the number of immunocompromised individuals in developing countries such as Uganda is much higher because of ailments ranging from opportunistic diseases, inadequate housing and malnutrition (Hazen 1988) especially in children. C. violaceum has been reported to have more severe effects on people in a state of malnourishment, immune deficiency and who are immunocompromised (Macher et al 1982;Bilton & Johnson 2000;Moore et al 2001). Additionally, the poor access to sanitation and safe water service in some lowincome areas in both rural and urban Uganda has been linked to waterborne disease outbreaks and is a cause of concern (Legros et al 2000;Tumwine et al 2002).…”
Section: Introductionmentioning
confidence: 99%